2008
DOI: 10.1097/tp.0b013e318183eefa
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Human Allograft Arterial Injury by Atorvastatin or Simvastatin Correlates With Reduction of Interferon-γ Production by Infiltrating T Cells

Abstract: Background Graft arteriosclerosis (GA) is an important factor limiting long-term outcomes after organ transplantation. We have used a chimeric humanized mouse system to model this arteriopathy in human vessels and found the morphologic and functional changes of experimental GA to be interferon (IFN)-γ-dependent. This study evaluated if HMG-CoA reductase inhibitors, described as inhibitors of IFN-γ production, affect GA in our model. Methods C.B-17 SCID/beige mice were transplanted with human artery segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Previous studies indicated that T‐cells‐derived IFN‐γ is responsible for increased proliferation of VSMCs in transplanted arteries [Wang et al, ; Yu et al, ]. Similarly, in animal models of vascular wound repair, genetic ablation or pharmacological blockade of IFN‐γ leads to decreased inflammatory response and impaired VSMC proliferation, accompanying with attenuated neointimal formation [Yi et al, ; Hirata et al, ]. In this study, we now additionally show that IFN‐γ signaling is critically involved in modulating VSMC phenotypic switch from the contractile state to the synthetic state, which is indicated by reduced expression of SMC‐specific markers including SM22α and calponin.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies indicated that T‐cells‐derived IFN‐γ is responsible for increased proliferation of VSMCs in transplanted arteries [Wang et al, ; Yu et al, ]. Similarly, in animal models of vascular wound repair, genetic ablation or pharmacological blockade of IFN‐γ leads to decreased inflammatory response and impaired VSMC proliferation, accompanying with attenuated neointimal formation [Yi et al, ; Hirata et al, ]. In this study, we now additionally show that IFN‐γ signaling is critically involved in modulating VSMC phenotypic switch from the contractile state to the synthetic state, which is indicated by reduced expression of SMC‐specific markers including SM22α and calponin.…”
Section: Discussionsupporting
confidence: 73%
“…Our findings suggest that PPAR γ agonists have the capacity to suppress memory alloreactive T cells responsible for vascular graft rejection via a PPAR γ -dependent mechanism. Interestingly, in the present study, we show complete prevention of neointima formation by pioglitazone; in our previous study testing the effects of statins, 48 we reported a reduction in but not complete inhibition of T cell–driven arterial remodeling. The PPAR γ agonists are approved for treatment of type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 53%
“…In an in vivo model of graft arterial disease, statins were shown to decrease IFN-γ expression by T cells within the grafts (37). The ability of statins to reduce IFNG expression in each of 4 human T cell preparations was suppressed when KLF2 upregulation was blocked, establishing a causal link between the statin effects on T cell function and on KLF2 upregulation.…”
Section: Figurementioning
confidence: 97%